2012
DOI: 10.1186/1471-2393-12-68
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming phase 1 delays: the critical component of obstetric fistula prevention programs in resource-poor countries

Abstract: BackgroundAn obstetric fistula is a traumatic childbirth injury that occurs when labor is obstructed and delivery is delayed. Prolonged obstructed labor leads to the destruction of the tissues that normally separate the bladder from the vagina and creates a passageway (fistula) through which urine leaks continuously. Women with a fistula become social outcasts. Universal high-quality maternity care has eliminated the obstetric fistula in wealthy countries, but millions of women in resource-poor nations still e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
62
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(65 citation statements)
references
References 122 publications
3
62
0
Order By: Relevance
“…One article relied on the WHO's definition of prolonged labour as labour lasting over 24 hours, while noting that in rural settings there are misconceptions as to the ‗normal' length of labour 21 . Six articles detailed that standards set by the WHO are well understood by skilled birth attendants, however, most women in rural settings either deliver by themselves, in the company of family members, or with the aid of traditional birth assistants and are not aware that urgent obstetric care is needed past that point 1,3,11,14,19,21 . One study showed that in some settings, prolonged labour was not considered of enough importance to seek skilled medical care until two to five days had passed 21 .…”
Section: Prolonged Labourmentioning
confidence: 99%
See 3 more Smart Citations
“…One article relied on the WHO's definition of prolonged labour as labour lasting over 24 hours, while noting that in rural settings there are misconceptions as to the ‗normal' length of labour 21 . Six articles detailed that standards set by the WHO are well understood by skilled birth attendants, however, most women in rural settings either deliver by themselves, in the company of family members, or with the aid of traditional birth assistants and are not aware that urgent obstetric care is needed past that point 1,3,11,14,19,21 . One study showed that in some settings, prolonged labour was not considered of enough importance to seek skilled medical care until two to five days had passed 21 .…”
Section: Prolonged Labourmentioning
confidence: 99%
“…Six articles associated the development of fistulas with prolonged labour 2,12,13,19,21,23 , which they defined as the prolonged presence and pressure of the fetus against the soft tissues that separate the vagina from the bladder and/or the rectum, leading to their degeneration 26 . Crucially, the articles noted common divergence in understandings of the length of labour.…”
Section: Prolonged Labourmentioning
confidence: 99%
See 2 more Smart Citations
“…Phase I delays have been documented to be common in developing countries, including Sub -Saharan Africa (SSA [1][2][3]. A phase I delay is that caused by the patient's reluctance to seek medical attention [4].…”
Section: Introductionmentioning
confidence: 99%